A Randomized Impact Evaluation of Capturing Kids' Hearts, South Carolina, 2016-2018 - Hanson, Thomas ([Verlag nicht ermittelbar], 2021)
Funded by the National Institute of Justice, and in collaboration with the Flippen Group, the South Carolina Department of Education, and the districts of Charleston, Georgetown, Greenville, and Richland County Schools, WestEd conducted a randomized controlled trial of violence prevention and a school climate improvement program known as Capturing Kids' Hearts Campus by Design (CKH). CKH is a skill intensive, systematic process, whole-school intervention, designed to strengthen students' connectedness to school through enhancing protective factors (strong bonds with teachers, clear rules of conduct that are consistently enforced) and targeting modifiable risk factors (inappropriate behavior, poor social coping skills). The CKH training program aims to address the mechanisms and processes of social skills instruction that lead to improved student behavior by promoting skills acquisition (i.e., modeling, coaching, and behavioral rehearsal), enhancing skills performance, removing competing behavior, and facilitating maintenance of social skills. Components of CKH have been widely used throughout the United States. As of 2013, CKH training has been offered to over 200,000 staff in more than 7,000 schools. Although widely used, the whole package of CKH training and service has not been sufficiently subjected to a rigorous evaluation to assess the effectiveness of the program. The purpose of this study is to test and evaluate the Capturing Kids' Hearts package of programs and processes offered in the school-wide model, CKH Campus by Design, which includes Capturing Kids' Hearts, Process Champions-Plus, Campus TrAction Pacs, Teen Leadership, CKH Recharged, and Leadership Blueprint.